Asthma–chronic obstructive pulmonary disease overlap syndrome: a controversial concept. Issue 1 (February 2017) - Rodrigo, Gustavo J.; Neffen, Hugo; Plaza, Vicente
Abstract : Purpose of review: To illustrate the scant evidence and the shortcomings of the concept of 'asthma-COPD overlap syndrome' (ACOS) in terms of clinical utility. Recent findings: Asthma and chronic obstructive pulmonary disease (COPD) are considered as two distinct and heterogeneous diseases. For many years, physicians have been aware that asthma and COPD can coexist in some patients. Recently, the term ACOS has been applied when a person has clinical features of both asthma and COPD. However, the lack of an accurate diagnosis has led to inconsistent data regarding reported prevalence, prognosis and therapeutics. Even today, it has not been possible to establish a phenotypic characterization of ACOS, although it is part of the overall complexity and heterogeneity of COPDs. No high quality data exist on which to base treatment recommendations for ACOS. Consequently, in clinical practice, treatment is extrapolated from the available evidence on asthma and COPD. Summary: The current concept of ACOS seems clinically irrelevant because it has no influence on the prognosis and treatment of these patients. The authors concluded that the term ACOS should be avoided in the case of patients with features of both asthma and COPD.